Modelo ProLab EstacioNet, una propuesta para solucionar el problema de falta de estacionamiento en el Perú - Cadillo Navarro, Abel Yilber (2024)
It has been identified that Lima and other cities in Peru have grown in population and vehicle fleet, but they have not grown in infrastructure or parking spaces. Therefore, currently when looking for where to park a vehicle, various risks arise, such as not finding an authorized parking space and not having any other alternative to do it in a place that is not one, which has consequences such as fines and the possibility of being towed by a tow truck from the local municipality, generating additional costs and loss of time for the driver. Likewise, there are risks of robberies, robberies and damage to property, because the streets have a high crime rate. On the other hand, there are private spaces that are underused by citizens, who generally require additional income to improve their quality of life. Taking these two facts into account, and through the application of the methodology of the meta-user canvases and the user experience map, to adequately identify the problem as well as the most appropriate solution, this project is proposed, called EstacioNet. , which through the development of a digital web platform and a mobile application, will allow people to offer and reserve parking on demand in different parts of the cities of our country. By implementing this solution, sustainable development goals 9 and 11 would be achieved. With EstacioNet it is estimated to achieve an NPV of S/ 1,643,509 and an IRR of 213% in five years, considering a moderate average growth.